2003
DOI: 10.4049/jimmunol.170.6.3408
|View full text |Cite
|
Sign up to set email alerts
|

Prothrombin Binds to the Surface of Apoptotic, But Not Viable, Cells and Serves as a Target of Lupus Anticoagulant Autoantibodies

Abstract: Anti-phospholipid Ab (aPL) are a heterogeneous group of autoantibodies directed against various combinations of phospholipids (PL) and PL-binding proteins. Lupus anticoagulant (LA) Ab, a subset of aPL, exhibit anticoagulant properties in vitro, but are procoagulant in vivo. Most LA Ab are specific for either β2-glycoprotein I (β2GPI) or prothrombin (PT), two PL-binding proteins. We have previously shown that β2GPI and β2GPI-dependent aPL bind specifically to apoptotic, but not viable, thymocytes. In this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 41 publications
2
37
0
Order By: Relevance
“…These mAb were derived from mice immunized with phospholipid/PT complexes, comprised of either dioleoylphosphatidylserine (DOPS) and PT, or DOPS/ dioleoylphosphatidylcholine (DOPC) and PT, respectively. Both mAb exhibited similar and strong LA activity ( Table 1) that was dose-dependent and specifically inhibited by hexagonal (II) phase PE [27]. Neither mAb reacted with cardiolipin, DOPS, DOPC, or β2GPI in enzyme-linked immunoassay (ELISA) ( Table 1).…”
Section: Pt-dependent Monoclonal La Antibodies Bind To Apoptotic Cellsmentioning
confidence: 99%
See 4 more Smart Citations
“…These mAb were derived from mice immunized with phospholipid/PT complexes, comprised of either dioleoylphosphatidylserine (DOPS) and PT, or DOPS/ dioleoylphosphatidylcholine (DOPC) and PT, respectively. Both mAb exhibited similar and strong LA activity ( Table 1) that was dose-dependent and specifically inhibited by hexagonal (II) phase PE [27]. Neither mAb reacted with cardiolipin, DOPS, DOPC, or β2GPI in enzyme-linked immunoassay (ELISA) ( Table 1).…”
Section: Pt-dependent Monoclonal La Antibodies Bind To Apoptotic Cellsmentioning
confidence: 99%
“…Recently, we have also shown that this paradigm for recognition of apoptotic cells by aPL can be extended to prothrombin (PT)-dependent aPL [27]. We review some of these findings here, and propose that this paradigm may apply to other aPL.…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations